2008
DOI: 10.1242/jcs.032573
|View full text |Cite
|
Sign up to set email alerts
|

The ENTH and C-terminal domains ofDictyosteliumepsin cooperate to regulate the dynamic interaction with clathrin-coated pits

Abstract: Epsin contains a phospholipid-binding ENTH domain coupled to C-terminal domain motifs that bind coated pit proteins. We examined how these domains interact to influence epsin function and localization in Dictyostelium. Although not required for global clathrin function, epsin was essential for constructing oval spores during development. Within the epsin protein, we found that features important for essential function were distinct from features targeting epsin to clathrin-coated pits. On its own, the phosphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 53 publications
2
31
0
Order By: Relevance
“…While we and others have demonstrated a UIMmediated interaction of epsin with ubiquitinated proteins (6,7,22), the precise effect of epsin on Notch ligands traffic, as well as the mechanisms through epsin-dependent traffic of such ligands may affect Notch activation in the signal receiving cell remain to be elucidated. Actions of epsin independent of clathrin, and mediated by its ENTH domain only (11,49), also need to be understood. In conclusion, this study demonstrates that epsin 1 and 2 are dispensable for basic aspects of clathrinmediated endocytosis and support a cargo-specific function of these endocytic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we and others have demonstrated a UIMmediated interaction of epsin with ubiquitinated proteins (6,7,22), the precise effect of epsin on Notch ligands traffic, as well as the mechanisms through epsin-dependent traffic of such ligands may affect Notch activation in the signal receiving cell remain to be elucidated. Actions of epsin independent of clathrin, and mediated by its ENTH domain only (11,49), also need to be understood. In conclusion, this study demonstrates that epsin 1 and 2 are dispensable for basic aspects of clathrinmediated endocytosis and support a cargo-specific function of these endocytic factors.…”
Section: Discussionmentioning
confidence: 99%
“…In Dictyostelium, epsin is dispensable for clathrin-mediated endocytosis (11). In Drosophila, the only epsin ortholog, liquid facets, was shown to have a critical role in the Notch signaling pathway most likely via a specific endocytic function in Notch ligands expressing cells (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…For instance, genetic studies in yeast and Dictyostelium discoideum showed that the N-terminal ENTH domains of Ent1p (45) and epnA (46), respectively, which are epsin 1 orthologs, are sufficient for the cellular function of these epsins, although the C-terminal regions are also necessary for protein-protein interactions and localization. Our results showing that the K23E/ E42K mutation that disrupts the self-association of the ENTH domain abrogates the cellular endocytic function of the fulllength epsin 1 strongly suggest that the ENTH domain mainly accounts for the physiological activity of epsin 1 and that the self-association of the membrane-bound ENTH domain is essential for the physiological activity of epsin 1.…”
Section: Discussionmentioning
confidence: 99%
“…To test this notion, we performed in vitro GST pull-down experiments with recombinant GST-ANTH and ENTH proteins. We also tested the possible interaction between the GST-ANTH domain and the ENTH domain carrying a T104A point mutation, which interferes with epsin function but is not involved in lipid binding (20,26,27). We did not detect any binding between GST-ANTH and ENTH or ENTH T104A (Fig.…”
Section: Ent1 Enth and Sla2 Anth Domains Interact To Bind The Membranementioning
confidence: 94%
“…In vitro, the ENTH T104A domain did not enhance the binding of the Sla2 ANTH domain to liposomes, nor did it bind to ANTH in the presence of the PI(4,5)P 2 ligand, although by itself it showed the same PI(4,5)P 2 -binding properties as wild-type ENTH. The conserved surface threonine 104, which lies outside the PI(4,5) P 2 -binding pocket of Ent1 ENTH and was shown to be important for epsin function (20,26,27), may be a part of an interaction surface between the Ent1 ENTH and Sla2 ANTH domains. Notably, the localization of the ENTH domain of Ent2 to the endocytic site also depends on the Sla2 ANTH domain and the identical threonine residue of Ent2 ENTH, suggesting that the ENTH domains of both Ent1 and Ent2 can interact similarly with Sla2 ANTH.…”
Section: Sla2∆thatch-acb-gfp Ent1∆acbmentioning
confidence: 99%